Forms of intermediality in the novels of M. Bulgakov The Master and Margarita and B. Pasternak Doctor Zhivago - Алексєєва, Ніна Сімонівна (The Journal of V. N. Karazin Kharkiv National University. Series “Philology”, 2020)
The article focuses on analyzing such forms of intermediality as theatricality and carnival in the novels of M. Bulgakov The Master and Margarita and B. Pasternak Doctor Zhivago, intermediality being considered as an aspect of interdiscursivity. Theatricality in both novels is realized through the availability of «theatrical» vocabulary, theatric imagery and symbolism, and at the levels of the text structure and chronotope as well. The research shows that theatricality in Pasternak is of  intimate, impressionistic character, while that in Bulgakov is explicit  and features a carnival component. A common “theatrical” element in both novels is the motif of directing and the image of director. In Pasternak the director is life itself, unlike in Bulgakov, where life is directed by supernatural forces. In both novels the characters are actors and viewers at the same time, the stage and the floor of the house belong in the town. However, in Bulgakov, by contrast with Pasternak, there is no division of the town space. Theater in The Master and Margarita is related to the so called anticarnival, as it is conducted by the carnivalizer (Voland), rather than people. In Pasternak the unity «theatre  ̶  life  ̶  death» is a natural manifestation of life, unlike in Bulgakov, where the motif combination «theаter  ̶  death» has an ominous and violent character. In Doctor Zhivago the final  ruination of theatricality is of realistic character, while in The Master and Margarita it is of transcendent one. By and large it is possible to conclude that theatricality in Doctor Zhivago reminds of the theater of experience, when Bulgakov’s buffoonery is similar to the theater of performance.